Regulation and control of the Internet : is it feasible? Is it necessary? - BURTON, Paul F. (1995)
Presents the result of a two-part survey which tried to assess whether at a time when serious questions about the content of the Net are being raised, there is any truth in the claim that self-regulation is not only desirable but the only feasible solution. Topics examined for the survey were: abortion, drugs, war and pornography.